Економіко-математична модель формально утворених цін в електроенергетиці - Dobrovolsky V.K. (General Energy Institute of the National Academy of Sciences of Ukraine, 2000)
Economic and mathematical model of formally formed prices for power sector is presented. Mathematically the model is a linear programming problem with a specific structure, supplemented by algorithms for input data processing and problem optimal solutions. A numeric example is elaborated with data comparable to real one. The prices are calculated for various consumers' groups on voltage and different time ranges over 24-hour period. These formally formed prices can be used for working out the electricity tariffs.